'Am I an easy unit?' Challenges of being and becoming an activist teacher educator in a neoliberal Australian context. Issue 1 (2nd January 2021) - Luguetti, Carla; McLachlan, Fiona
ABSTRACT: Over the past decades, a body of scholarship has highlighted the possibilities of critical pedagogies in Health and Physical Education Teacher Education (HPETE) (Fitzpatrick, 2018 . What happened to critical pedagogy in physical education? An analysis of key critical work in the field. European Physical Education Review, 1–18; O'Sullivan, 2018 . PETE academics as public intellectuals and activists in a global teacher education context. Physical Education and Sport Pedagogy, 23 (5), 536–543; Walton-Fisette & Sutherland, 2018 . Moving forward with social justice education in physical education teacher education. Physical Education and Sport Pedagogy, 23 (5), 461–468). Although we have a body of research on social justice and critical pedagogy in HPETE, there is much to learn about the challenges activist teacher educators face in the process of being and becoming activists, especially in neoliberal contexts. This collaborative self-study explores the challenges of being and becoming an activist teacher educator in a neoliberal Australian context and how those challenges were negotiated. Participants included the lead researcher and a critical friend. Data collected included: (a) lead researcher observations collected as field notes; (b) lead researcher reflective diaries after each teaching episode; (c) meetings between the lead researcher and the critical friend; (d) material produced in the lead researcher's classes. Data analysis involved induction and constant comparison. The lead author faced internal and external challenges. First, the lead author had to negotiate her struggles to share power with students. The teacher educator started to be seen as a 'very cool person', teaching 'an easy unit'. Second, the teacher educator struggled to understand the complexities of teaching in a neoliberal context. The teacher educator [with the help of the critical friend] negotiated those challenges by understanding the importance to set expectations for learning within an activist approach and understanding the power of activist approaches to challenge a neoliberal system. Future studies should continue to explore the challenges activist teacher educators face in a context where students are socialized in neoliberal context, and educator's performance is measured in the same system.